Clusterin expression in nontumor tissue in patients with resectable hepatocellular carcinoma related with postresectional survival. Issue 12 (December 2019) - Kuo, Po-Chung; Chau, Ivy Yenwen; Li, Anna Fen-Yau; Chau, Yat-Pang; Hsia, Cheng-Yuan; Chau, Gar-Yang
Abstract : Background: Surgical resection offers an effective treatment for patients with hepatocellular carcinoma (HCC); however, it has high tumor recurrence rate. Clusterin is a highly conserved glycoprotein that enhances cell aggregation in vitro. It is upregulated in several types of cancers such as breast, ovarian, colon, prostate and kidney cancers, and HCC. Clusterin overexpression is correlated with tumor metastasis. We evaluated the significance of clusterin expression levels in serum and resected tissues of patients with HCC. Methods: Serum, resected tumor tissue, and nontumor tissue were collected from 140 patients with HCC undergoing hepatic resection. Serum clusterin levels were determined by enzyme-linked immunosorbent assay. Clusterin expression in resected tissue was evaluated by immunohistochemistry. Median follow-up time was 57.8 months. Results: Mean serum clusterin levels were found to be 130.0 ± 58.7 µg/mL (range, 10.1-366.6 µg/mL). Serum clusterin levels were independent of tumor stage and deterioration of liver function in patients. No significant difference was observed in the survival of patients with high (>130.0 ± 58.7 µg/mL) or low (⩽130.0 ± 58.7 µg/mL) serum clusterin level. Clusterin was expressed in HCC tissues of 76 patients (54.3%) and nontumor liver tissues of 53 patients (37.9%). No significant difference was observed in the survival of patients with positive or negative clusterin expression in HCC tissues. In nontumor tissues, patients with positive clusterin expression were observed to have low postoperative disease-free survival rate ( p = 0.001) compared to patients with negative clusterin expression. Multivariate analysis showed that tumor with macrovascular/microvascular invasion and clusterin expression in nontumor tissues are independent prognostic factors following hepatic resection. Conclusion: In HCC, clusterin expression in nontumor tissue shows worse prognosis after hepatic resection. Clusterin can be a prognostic marker for patients with postresection HCC.